Effect of high-intensity training on improving knee flexion strength and quality of life in patients with knee osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Zhai, Bo; Wang, Yu; Zhang, Zhongliang; Wang, Qiang (Frontiers in Physiology, 2025)
ObjectivesWhether high-intensity exercise can effectively improve the symptoms and quality of life of patients with knee osteoarthritis has not been determined. This study updates the evidence on the efficacy of high-intensity training for patients with knee osteoarthritis by integrating all large-scale randomized controlled trials (RCTs).MethodsA systematic literature search was conducted in PubMed, Embase, Web of Science, and Cochrane through November 2024. Outcomes assessed included Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), 6-min walk test (6-MWT), knee flexion strength, knee extension strength, leg press strength, Knee Injury and Osteoarthritis Outcome Score (KOOS) (pain, symptoms, and QoL), stair climbing test, and timed-up-and-go (TUG). Standardized mean differences (SMD) with 95% confidence intervals (CI) were used to pool continuous variables. Sensitivity analysis was performed to assess result stability. Analyses were conducted using Review Manager 5.4 and STATA 15.1.ResultsNine RCTs with 1,540 patients were included. The average age of the patients ranged from 59.1 to 69 years. Meta-analysis showed significant improvements in knee flexion strength (SMD: 0.39; 95% CI: 0.08, 0.70), leg press strength (SMD: 0.47; 95% CI: 0.23, 0.70), KOOS symptoms (SMD: 0.18; 95% CI: 0.02, 0.35), and KOOS QoL (SMD: 0.29; 95% CI: 0.13, 0.45) in the high-intensity exercise group compared to the control. However, high-intensity exercise had no significant effect on WOMAC, 6-MWT, knee extension strength, KOOS pain, stair climbing, or TUG.ConclusionHigh-intensity exercise significantly improves knee flexion strength, leg press strength, and KOOS symptoms and QoL in knee osteoarthritis patients. Given the study’s limitations, further large-scale, multicenter RCTs are needed to confirm the rehabilitation effects and potential influencing factors of high-intensity exercise.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/